Personalized at-home autologous hematopoietic stem cell transplantation during the SARS-CoV-2 outbreak. (July 2021) - Martínez-Roca, Alexandra; Rodríguez-Lobato, Luis Gerardo; Ballestar, Nuria; Gallego, Cristina; Fernández-Avilés, Francesc
Highlights: SARS-CoV-2 health crisis forced institutions to place a hold on most non-priority healthcare activities. At-home autologous stem cell transplant may present as an option to continue to perform this procedure. At-home autologous stem cell transplant presents as a safe option for patients in a pandemic state.